2018
DOI: 10.1177/0361198118798721
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure-Based Random Finite Element Method Simulation of Frost Heave: Theory and Implementation

Abstract: Frost heave can cause serious damage to civil infrastructure. For example, interactions of soil and water pipes under frozen conditions have been found to significantly accelerate pipe fracture. Frost heave may cause the retaining walls along highways to crack and even fail in cold climates. This paper describes a holistic model to simulate the temperature, stress, and deformation in frozen soil and implement a model to simulate frost heave and stress on water pipelines. The frozen soil behaviors are based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Zhan et al analyzed the variations in the temperature field, liquid water migration, solid ice accumulation, and frost heave deformation of frozen soil slopes [13]. Dong and Yu proposed a numerical model to simulate the frost heave and stress of water pipes and performed experiments to confirm the reliability of the model at simulating the temperature distribution and volume variation [14]. Chou et al, Zhao et al, Han et al, and Feng et al used the software Geo-Studio and demonstrated that the thawing depth of slopes subjected to freeze thaw cycles increased with the freezing depth and that a closed loop isotherm formed on the slope [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Zhan et al analyzed the variations in the temperature field, liquid water migration, solid ice accumulation, and frost heave deformation of frozen soil slopes [13]. Dong and Yu proposed a numerical model to simulate the frost heave and stress of water pipes and performed experiments to confirm the reliability of the model at simulating the temperature distribution and volume variation [14]. Chou et al, Zhao et al, Han et al, and Feng et al used the software Geo-Studio and demonstrated that the thawing depth of slopes subjected to freeze thaw cycles increased with the freezing depth and that a closed loop isotherm formed on the slope [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…From the viewpoint of the energy conservation law, mass conservation law, and the principle of static equilibrium considering water/ice phase change, Huang et al [13] set up a fully coupled THM model and verified its validity with the laboratory test. Based on a microstructure-based random finite element model for the frozen soil, Dong and Yu [14] established a holistic model to simulate the temperature, stress, and deformation in frozen soil and implement a model to simulate frost heave and stress on water pipelines. In order to consider the migration of unfrozen water during freezing, Wang et al [15] proposed a general thermo-mechanical-water migration coupled constitutive model to model mechanical degradation of rocks subjected to freeze-thaw cycles.…”
Section: Introductionmentioning
confidence: 99%